Stress intensity factors for through clad and underclad defects in a WWER type reactor pressure vessel in pressurised thermal shock analysis (Fracture and Structural Integrity, 2026)
This study develops stress intensity factor (SIF) solutions for cladded WWER reactor pressure vessel nozzles subjected to pressurised thermal shock loading. Although finite element analysis is widely used for fracture assessment, analytical or semi-analytical SIF formulations remain important for fast evaluation, including online stress monitoring, probabilistic fracture mechanics, and screening of transient scenarios. The proposed approach combines an influence coefficient method based on three-dimensional finite-element J-integral evaluation with least-squares refinement of shape coefficients. A stress decomposition procedure is applied to address the stress discontinuity at the ferritic base metal–austenitic cladding interface. The resulting coefficients are validated against finite element reference solutions for representative pressure and thermal loading cases and show good agreement over the investigated range of crack sizes and aspect ratios. The developed solutions provide a practical tool for engineering assessment of through-clad and underclad defects in cladded WWER nozzle regions.
Keywords: PTS analysis; polynomial solution; stress intensity factor; nuclear reactor; fracture of the cladded component